NEGOSIASI DIPLOMASI BUDAYA K-POP DI INDONESIA: STUDI KASUS BOIKOT PENGGEMAR ATEEZ - Febryana, Dhannya (Multikultura, 2026)
This study examines the boycott by Indonesian fans against the K-pop group ATEEZ as part of the dynamics of South Korea’s cultural diplomacy in Southeast Asia. Building on the understanding of K-pop as an important instrument of soft power in South Korea’s cultural diplomacy strategy, this research highlights how regional audiences do not always passively accept such practices. Using a qualitative approach with digital discourse analysis, the study analyzes boycott-related discourses circulating on social media and in online news coverage to explore the narratives, meanings, and cultural implications of this action. The fan boycott is not merely an expression of emotional disappointment, but a form of fan activism constructed through narratives of fan contribution, regional inequality, and demands for symbolic recognition. Through digital media, Indonesian fans position themselves as non-state actors with agency in negotiating cultural relations with the K-pop industry. These findings reveal the limitations of cultural diplomacy that relies solely on global market logic and underscore that the effectiveness of soft power depends on the quality of fair and inclusive relationships with regional audiences. This study is expected to contribute to the field of cultural diplomacy by positioning Southeast Asian audiences as active subjects in the negotiation of soft power through popular culture.